Nickel-Catalyzed Cross-Electrophile Coupling Reactions of Alcohols and Their Derivatives - Jana, Sayan K.; Maji, Biplab (Synthesis, 2025)
Nickel-catalyzed cross-electrophile coupling of halide coupling partners has emerged as a powerful tool for constructing C–C bonds under mild conditions. However, the limited availability of halide coupling partners means that a significant portion must be synthetically prepared, which can pose sustainability challenges. In this context, aryl and alkyl alcohols represent highly promising alternative coupling partners due to their abundance and versatility. Despite their potential, the application of alcohols in cross-electrophile coupling reactions is mostly explored in couplings with aryl or alkyl halide derivatives. Cross-coupling reactions in which both coupling partners are alcohols or derivatives remained underexplored until recent advancements. This short review aims to highlight the current progress in nickel-catalyzed cross-electrophile coupling of alcohols and their derivatives, and discusses future opportunities in this burgeoning field.1 Introduction2 Nickel-Catalyzed Cross-Electrophile Coupling Using Alcohols or Alcohol Derivatives2.1 C(sp3)–C(sp3) Cross-Coupling2.2 C(sp2)–C(sp3) Cross-Coupling2.3 C(sp2)–C(sp2) Cross-Coupling3 Cross-Coupling Reactions of Alcohols via Hydrogen Transfer Reactions4 Summary and Outlook
Keywords: nickel catalysis; cross-electrophile coupling; alcohol coupling partners; cross selectivity; sustainable approach; naturally abundant